Prostitutes and Brides? - Arunachalam, Raj; Shah, Manisha (American Economic Review, 2008)
In a seminal paper, Lena Edlund and Evelyn Korn (2002) introduce a puzzling stylized fact? that prostitution is low-skilled, labor intensive, female, and well paid?and offer a provocative explanation: sex workers draw a compensating differential due to the foregone opportunity to sell their fertility in the marriage market. In so doing, they not only provide the first formal model of occupational choice involving prostitu? tion, they also draw an intriguing link between the labor market and the marriage market that holds for only one occupation. When a woman chooses to become a sex worker, she relinquishes the compensation she would otherwise receive in marriage, since taboos prevent prostitutes from marrying. Thus, even in settings where prostitu? tion is legal, it must draw an earnings premium. Beyond drawing considerable media attention, the richness of the Edlund-Korn model has made